2008
DOI: 10.1128/jcm.01593-07
|View full text |Cite
|
Sign up to set email alerts
|

Rare AU-1-Like G3P[9] Human Rotaviruses with a Kun-Like NSP4 Gene Detected in Children with Diarrhea in Italy

Abstract: Three G3P[9] rotaviruses, detected in children hospitalized with gastroenteritis in Palermo, Italy, were found to be genetically related to strains of either human or feline origin in the VP7, VP4, and VP6 genes. In contrast, in the NSP4 gene the viruses resembled G2P[4] human strains, suggesting a reassortment between AU-1-like and Kun-like strains.Group A rotaviruses are a major cause of acute gastroenteritis in humans and animals (14). The rotavirus genome is composed of 11 segments of double-stranded RNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Likewise, strains R113 and R142 presented human-feline-canine G9-P[9]-I1-E2 and G3-P[9]-I2-E2 profiles, respectively. This unusual G3-P[9]-E2 profile has been observed in three rotavirus strains detected in Italy [De Grazia et al, 2008] and suggests a reassortment between AU-1-like and Kunlike strains. Three strains possessed the profiles G3-P[9]-I1-E1 (R52 and R56) and G1-P[9]-I1-E1 (R70), suggesting a reassortment between AU-1-like and Walike strains.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Likewise, strains R113 and R142 presented human-feline-canine G9-P[9]-I1-E2 and G3-P[9]-I2-E2 profiles, respectively. This unusual G3-P[9]-E2 profile has been observed in three rotavirus strains detected in Italy [De Grazia et al, 2008] and suggests a reassortment between AU-1-like and Kunlike strains. Three strains possessed the profiles G3-P[9]-I1-E1 (R52 and R56) and G1-P[9]-I1-E1 (R70), suggesting a reassortment between AU-1-like and Walike strains.…”
Section: Discussionsupporting
confidence: 51%
“…The I3-E3 profile is generally associated with feline-canine rotavirus strains, which are usually related to genotypes G3-P[3] or P[9] [Tsugawa and Hoshino, 2008]. Few rotavirus reassorted strains bearing human-felinecanine specificity have been reported [Taniguchi et al, 1989;Santos et al, 2001;Khamrin et al, 2007;De Grazia et al, 2008]. The human G3-P[9]-I3-E3 prototype strain AU-1 has been demonstrated to be closely related to feline-canine rotavirus [Nakagomi et al, 1987;Nakagomi and Nakagomi, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that G3P [9] strains caused severe infection in two patients that required hospital treatment. This is consistent with the scarce data in the literature [13][14][15][16][17]22], indicating that G3P [9] strains cannot be considered as less virulent than other community strains. These findings could have implications in the vaccination era.…”
Section: Discussionsupporting
confidence: 93%
“…Human RVAs with genetic homology to feline RVAs have been isolated from widespread geographical locations, including Japan (12,13), Israel (14,15), Tunisia (16), and the United States (17). Additionally, putative human/feline reassortant rotaviruses have been identified in children in Italy (18).…”
mentioning
confidence: 99%